2001
DOI: 10.1093/jpepsy/26.6.343
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Psychological Adjustment in School-Age Children Infected With HIV

Abstract: Approximately 25% of children with HIV disease exhibited clinically significant emotional or behavioral problems; however, even higher rates of psychological adjustment problems were found in healthy children. Children with HIV disease who have not been told their diagnosis and children who endorse more emotion-focused coping strategies tend to exhibit more psychological adjustment problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
100
2
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 18 publications
9
100
2
3
Order By: Relevance
“…Children with other illnesses, such as cancer, have been found to be at risk of emotional and behavioral difficulties resulting from disclosure. [19][20][21] Others have found that children benefit from an open discussion of their illness and that nondisclosure does not necessarily protect them from psychological distress. [22][23][24] HIV-infected children in industrialized countries fared well after disclosure, and better than children who were unaware of their HIV infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with other illnesses, such as cancer, have been found to be at risk of emotional and behavioral difficulties resulting from disclosure. [19][20][21] Others have found that children benefit from an open discussion of their illness and that nondisclosure does not necessarily protect them from psychological distress. [22][23][24] HIV-infected children in industrialized countries fared well after disclosure, and better than children who were unaware of their HIV infection.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] HIV-infected children in industrialized countries fared well after disclosure, and better than children who were unaware of their HIV infection. 1,19,25,26 While studies have looked at correlates of disclosure, few have investigated the process of disclosure to HIV-infected children specifically, particularly in developing countries. This study was, therefore, exploratory and focused on the experiences of infected children in a comprehensive HIV pediatric care and treatment program in Kinshasa, the Democratic Republic of the Congo (DRC).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, they are often burdened with the inability to confront their own mortality as well as that of their children. It is documented that childhood chronic illness brings about signiicant strain on the family system, including high rates of maternal depression and anxiety, marital distress and adjustment problems [5,6,55,56].…”
Section: Parental Health and Relationship To Caregivingmentioning
confidence: 99%
“…La plupart des jeunes rapportaient que leur vie s'était détériorée depuis cette annonce (Wiener et al, 1996). Elle aurait aussi engendré chez les jeunes une détresse psychologique (Bachanas et al, 2001;Lester et al, 2002;Mellins et al, 2002;New et al, 2003;Riekert et al, 1999;Wiener et al, 1996). Suite à ce dévoilement, les parents ont constaté que leurs enfants étaient devenus inquisitifs, colériques, anxieux, déprimés ou tristes (Blasini et al, 2004).…”
Section: Les Répercussions Psychologiques Et Sociales Du Dévoilement unclassified
“…Toutefois, six mois après l'annonce, plusieurs des jeunes infectés par le VIH ont affirmé se sentir normaux et considéraient le dévoilement comme un événement positif (Blasini et al, 2004). D'autres études avancent, à l'inverse, que le dévoilement du diagnostic réduirait la prévalence de symptômes dépressifs et anxieux chez l'enfant séropositif (Bachanas et al, 2001;Battles et Wiener, 2002;Mellins et al, 2002;Riekert et al, 1999). Ces contradictions dans les résultats des différentes études pourraient être dues aux écarts d'âge des jeunes interrogés et le temps écoulé depuis l'annonce du diagnostic.…”
Section: Les Répercussions Psychologiques Et Sociales Du Dévoilement unclassified